Charcoal burning, Trinidad - (:unkn) unknown (Printed in England, 2009)
Man making charcoal by burning bamboo in an earth covered pit. Description on the card is as follows: "Charcoal is largely used as fuel in Trinidad houses. It is made from wood of no values as timber, cut into lengths and burnt in an earth covered pit on the borders of the forest in picturesque surroundings."
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided
Keywords: Postcards; Trinidad and Tobago; Charcoal burners--Trinidad and Tobago